Formulation, optimization and evaluation of floating microspheres of hydrochlorothiazide - AMITHA SHETTY,; PANNEERSELVAM,; CHRISHMA SHALOMITH,; SMITHA H, (International Journal of Pharma and Bio Sciences, 2019)
The objective of the present study was to develop floating microspheres of hydrochlorothiazide in order to achieve extended retention in upper gastrointestinal tract which may enhance absorption and bioavailability. The microspheres were prepared by non-aqueous solvent evaporation method using different ratio of ethyl cellulose with drug in acetone. Fourier-transform infrared spectroscopy study shows that drug and other excipients are compatible with each other. The effects of polymers concentration on drug release profile were investigated. Response surface methodology was applied to systemically optimize the drug release profile. Polymer to drug ratio and stirring speed were selected as independent variables. Drug entrapment efficiency, percentage buoyancy and in-vitro drug release after 4 hours were selected as dependent variables. Obtained microspheres were subjected to different evaluation parameters such as percentage yield, particle size analysis, drug entrapment efficiency, percentage buoyancy, in-vitro drug release, drug release kinetics and scanning electron microscopy. The optimized formulation (FF10) showed satisfactory drug entrapment efficiency of 93.99±1.2 %, percentage buoyancy of 85.61±1.8 and percentage drug release after 4 hours of 24.3±0.25 %. Scanning electron microscopy analysis revealed that particles were spherical with smooth surface. Particles were flowing freely with average particle size of 166.7 μm. Accelerated stability study performed for three months also indicated that optimized formulation was stable. Better results were observed from optimized floating microspheres of hydrochlorothiazide and may prolong the drug release in stomach and improve the bioavailability of the drug.